A LEGAL ANALYSIS OF THE ROLE OF ECONOMIC LAW IN SUPPORTING DOMESTIC TRADE IN INDONESIA - Gunawan Widjaja (CV. Adiba Aisha Amira, 2026)
This study examines the role of economic law in supporting national trade in Indonesia through a literature review using a normative legal approach. Economic law is positioned as a vital instrument in creating legal certainty, justice, protection for business operators and consumers, and orderliness in national trade activities. The discussion indicates that Law No. 7 of 2014 on Trade serves as the primary foundation for regulating national trade, whilst the development of digital trade and globalisation demands more responsive regulatory adaptation. The findings also confirm that the implementation of economic law still faces a number of challenges, such as regulatory disharmony, weak supervision, infrastructure limitations, and the complexity of electronic-based trade. Therefore, the strengthening of economic law is necessary so that national trade can develop in an orderly, fair, and sustainable manner.